Oral Cancer: Knowledge, Attitudes and Practices of Users of the School of Dentistry at the Universidad de Antioquia, 2016 (Revista Nacional de Odontología, 2017)
Introduction: This article describes the knowledge, attitudes and practices of users of the School ofDentistry at the Universidad de Antioquia about oral cancer. Materials and methods: Study with a quantitative, descriptive approach; a collection instrument wasdesigned with which sociodemographic variables were ascertained, and the knowledge, attitudes andpractices of users of the School of Dentistry at the Universidad de Antioquia were evaluated. Results and discussion: Although most of the people surveyed stated that they are aware of the existence of oral cancer, they do not recognize the warning signs of oral cancer and how they can prevent it; these results do not vary in individuals who are taken care of at the School. Despite these results, most respondents examine themselves intra-orally, although they do not have clear instructions on how to do it. Conclusions: The fact that people ignore how to act against oral cancer despite recognizing its ex-istence is largely related to health professionals since, although the majority of respondents wereattended to at the School of Dentistry and even in other healthcare centers, their knowledge, attitudesand practices did not vary much from those of people who did not have access to these programs.Therefore, it is suggested that an educational strategy be implemented to increase the knowledge ofdetection and prevention of oral cancer, in which the dentist is the main actor.
Keywords: attitude; self-examination; knowledge; oral cancer; habit; practice; prevention